Regulation of ATMPs in Europe: present and future - Hidalgo-Simon, Ana (Henry Stewart Talks, 2021)
Introduction to ATMPs, Route of approval in Europe, Approved ATMPs 2009-2021, ATMPs: Challenges for regulators, Challenges to be addressed during development, What support tools developers can use, Future challenges of ATMPs, Potential bridges and solutions